Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

Selective imaging of quorum sensing receptors in bacteria using fluorescent Au nanocluster probes surface functionalized with signal molecules - Mukherji, Ruchira; Samanta, Anupam; Illathvalappil, Rajith; Chowdhury, Somak; Prabhune, Asmita; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2013)
Fluorescent ultrasmall gold clusters decorated with bacterial quorum sensing signal molecules, acyl homoserine lactone, are synthesized. These fluorescent probes are found to have emission in the near-infrared spectral region advantageous for bioimaging. Imaging studies using different. strains of bacteria with and without acyl homoserine lactone receptors with the aid of confocal microscopy have shown that the probe interacts preferentially with cells possessing these receptors. This indicates that, with appropriate surface functionalization, the Au clusters can be used for receptor specific detection with enhanced selectivity.
Keywords: Au nanoclusters; Biosensor; fluorescence imaging; quorum sensing

Controlled release of antimicrobial Cephalexin drug from silica microparticles - Rao, B. V. Bhaskara; Mukherji, Ruchira; Shitre, G.; Alam, F.; Prabhune, Asmita; Kale, Sangeeta N. (Materials Science & Engineering C-Materials for Biological Applications, 2014)
Release of antimicrobial drugs in a controlled fashion for extended duration of time has been investigated for long. Such controlled-drug-releasing materials show promising applications in medicinal bandages. Along with antimicrobial agents, one could also incorporate other therapeutic drugs, to make such bandages more versatile. In this context, silica micro particles were synthesized using direct reduction method, in which the synthesis was done in the presence of Cephalexin. Cephalexin was chosen as an antimicrobial candidate. The morphological characterization shows formation of monodispersed, silica microparticles of similar to 200 nm in size. The FTIR spectroscopy shows weak interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. Upon conjugation, the UV-vis spectroscopy shows persistence of the Cephalexin signature, especially its R group, confirming its antimicrobial activity even after conjugation. Loading studies reveal 12% Cephalexin loading on silica. The antimicrobial studies were done on three micro-organisms, namely, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Using zone-of-inhibition studies, it was found that E. coli, did not respond to the delivery of Cephalexin either directly or via microparticles. However, for both S. aureus and B. subtilis, the particles showed controlled release of Cephalexin for the duration of 48 h and continued maintenance and even increase in the zone of inhibition. This work demonstrates an effective protocol to prepare antimicrobial patches for controlled drug delivery. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial; Medicinal bandage; Silica microparticles; sustained drug release

New role for penicillin acylases: degradation of acyl homoserine lactone quorum sensing signals by Kluyvera citrophila penicillin G acylase - Mukherji, Ruchira; Varshney, Nishant Kumar; Panigrahi, Priyabrata; Suresh, C. G.; Prabhune, Asmita (Enzyme and Microbial Technology, 2014)
Use of penicillin acylases for the production of semi-synthetic penicillins is well-known. Escherichia coli penicillin G acylase (EcPGA) has been extensively used for this purpose; however, Kluyvera citrophila penicillin G acylase (KcPGA) is assumed to be a better substitute, owing to its increased resilience to extreme pH conditions and ease of immobilization. In the present article we report a new dimension for the amidase activity of KcPGA by demonstrating its ability to cleave bacterial quorum sensing signal molecules, acyl homoserine lactones (AHL) with acyl chain length of 6-8 with or without oxo-substitution at third carbon position. Initial evidence of AHL degrading capability of KcPGA was obtained using CV026 based bioassay method. Kinetic studies performed at pH 8.0 and 50 degrees C revealed 3-oxo-C6 HSL to be the best substrate for the enzyme with V-max and K-m values of 21.37+0.85 mM/h/mg of protein and 0.1+0.01 mM, respectively. C6 HSL was found to be the second best substrate with V-max. and K-m value of 10.06+0.27 mM/h/mg of protein and 0.28+0.02 mM, respectively. Molecular modeling and docking studies performed on the active site of the enzyme support these findings by showing the fitting of AHLs perfectly within the hydrophobic pocket of the enzyme active site. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acyl homoserine lactones; CV026; KcPGA; Quorum quenching

Novel glycolipids synthesized using plant essential oils and their application in quorum sensing inhibition and as antibiofilm agents - Mukherji, Ruchira; Prabhune, Asmita (Scientific World Journal, 2014)
Essential oils (EOs) form an important part of traditional medicine so their anti-microbial and, in the recent past, antiquorum sensing activity has been well studied. However it is likely that due to their hydrophobic nature and reduced solubility in aqueous environments full potential of their activity cannot be realized. hence it is only rational to formulate a process to make these molecules more polar in nature. The present paper reports synthesis of sophorolipids using 12 different essential oils as substrates, thus providing surfactant-like properties to these EOs. The synthesis protocol makes the use of Candida bombicola ATCC 22214 as producer organism. The production process required 7 days of incubation at 28 degrees C and 180 rpm. Preliminary characterization of the synthesized essential oil sophorolipids (EOSLs) was performed using thin layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR). Additionally, essential oils that were incapable of mediating quorum sensing inhibition (QSI) on their own became potent quorum sensing inhibitors upon conversion into their corresponding EOSLs. Antibiofilm potential of these EOSLs was also demonstrated using V. cholerae as test organism. Use of essential oils as substrates for glycolipid synthesis has not been attempted previously, and hence this is the first report.

New class of bacterial quorum sensing antagonists: glycomonoterpenols synthesized using linalool and alpha terpineol - Mukherji, Ruchira; Prabhune, Asmita (World Journal of Microbiology & Biotechnology, 2015)
With increasing burden of antibiotic resistant microorganism search for newer drug targets and potent drug molecules is a never ending scenario. Quorum sensing (QS), the phenomenon of bacterial cross-talk, is one such target that has captured the attention of many and has been touted as the future of new age antimicrobials. Quorum sensing has the potential to regulate a plethora of bacterial virulence phenotypes and search of molecules with powerful quorum sensing inhibitory (QSI) capacity are underway. Monoterpene alcohols like linalool and alpha terpineol have been shown to possess antimicrobial and anti-biofilm activity. However in this article we attempt to bring forth a new class of compounds, glycomonoterpenols, derived from monoterpenoids alcohols. These glycomonoterpenols have been synthesized using Candida bombicola ATCC 22214 by feeding the cells with linalool and alpha terpineol respectively as substrates in 10 % glucose, production medium. The advantage of these molecules over their parent compound is their additional surfactant like property, increased solubility and enhanced QSI potential. A variety of gram-negative bacteria capable of elaborating quorum sensing mediated phenotypes have been selected and both these glycoterpenoid derivatives have been shown to possess strong anti-QS activity.
Keywords: Alpha-terpineol; Glycomonoterpenols; Linalool; Pseudomonas aeruginosa; Quorum sensing inhibition

Possible correlation between bile salt hydrolysis and ahl deamidation: staphylococcus epidermidis RM1, a potent quorum quencher and bile salt hydrolase producer - Mukherji, Ruchira; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2015)
The aim of the present work was to isolate a bile salt hydrolase (BSH) producer from fermented soy curd and explore the ability of the BSH produced to cleave bacterial quorum sensing signals. Bacterial isolates with possible ability to deconjugate bile salts were enriched and isolated on De Man, Rogosa and Sharpe (MRS) medium containing 0.2 % bile salts. BSH-producing positive isolate with orange-pink-pigmented colonies was isolated and was identified as a strain of Staphylococcus epidermidis using biochemical and phylogenetic tools. S. epidermidis RM1 was shown to possess both potent BSH and N-acyl homoserine lactone (AHL) cleavage activity. Genetic basis of this dual-enzyme activity was explored by means of specific primers designed using S. epidermidis ATCC 12228 genome as template. It was observed that a single enzyme was not responsible for both the activity. Two different genetic elements corresponding to each of the enzymatic activity were successfully amplified from the genomic DNA of the isolate.
Keywords: AHL acylase; Bile salt hydrolase; CV026; Quorum quenching; Staphylococcus epidermidis

Sequence and structure-based comparative analysis to assess, identify and improve the thermostability of penicillin G acylases - Panigrahi, Priyabrata; Chand, Deepak; Mukherji, Ruchira; Ramasamy, Sureshkumar; Suresh, C. G. (Journal of Industrial Microbiology & Biotechnology, 2015)
Penicillin acylases are enzymes employed by the pharmaceutical industry for the manufacture of semi-synthetic penicillins. There is a continuous demand for thermostable and alkalophilic enzymes in such applications. We have carried out a computational analysis of known penicillin G acylases (PGAs) in terms of their thermostable nature using various protein-stabilizing factors. While the presence of disulfide bridges was considered initially to screen putative thermostable PGAs from the database, various other factors such as high arginine to lysine ratio, less content of thermolabile amino acids, presence of proline in beta-turns, more number of ion-pair and other non-bonded interactions were also considered for comparison. A modified consensus approach designed could further identify stabilizing residue positions by site-specific comparison between mesostable and thermostable PGAs. A most likely thermostable enzyme identified from the analysis was PGA from Paracoccus denitrificans (PdPGA). This was cloned, expressed and tested for its thermostable nature using biochemical and biophysical experiments. The consensus site-specific sequence-based approach predicted PdPGA to be more thermostable than Escherichia coli PGA, but not as thermostable as the PGA from Achromobacter xylosoxidans. Experimental data showed that PdPGA was comparatively less thermostable than Achromobacter xylosoxidans PGA, although thermostability factors favored a much higher stability. Despite being mesostable, PdPGA being active and stable at alkaline pH is an advantage. Finally, several residue positions could be identified in PdPGA, which upon mutation selectively could improve the thermostability of the enzyme.
Keywords: Alkalistable; beta-lactam antibiotics; Consensus approach; Disulfide bridge; Ion pairs; Penicillin acylase; Thermostability

Biological activity of sophorolipids and their possible use as antiviral agents - Borsanyiova, Maria; Patil, Amrita; Mukherji, Ruchira; Prabhune, Asmita; Bopegamage, Shubhada (Folia Microbiologica, 2016)
Sophorolipids are surface active glycolipids consisting of a hydrophilic sophorose unit and a hydrophobic portion composed of a fatty acid tail. Crude sophorolipid sample contains both acidic and lactonic forms of sophorolipid with different degrees of acetylation and varying lengths of the fatty acid chains depending on the substrates used in the production process. Carboxylic end in the acidic form of the fatty acid is free, whereas in the lactonic form, it is internally esterified. Sophorolipids show different physicochemical properties with wide range of applications for each structural compound. Lactonic form of sophorolipids shows surface tension reducing ability and biological activity, whereas the acidic form possesses better foam forming ability and higher solubility. Presence of acetyl groups gives hydrophilic nature to the sophorolipids which promotes its antiviral and cytokine-stimulating properties. The aim of this review is to explore and suggest the plausibility of sophorolipids as therapeutic and prophylactic agents for the treatment of viral diseases.

Biosynthesis of glycomonoterpenes to attenuate quorum sensing associated virulence in bacteria - Patil, Amrita; Joshi-Navre, Kasturi; Mukherji, Ruchira; Prabhune, Asmita (Biotechnology and Applied Biochemistry, 2017)
The acquisition of multidrug resistance in bacteria has become a bigger threat of late, mainly due to the bacterial signaling phenomenon, quorum sensing (QS). QS, among a population of bacteria, initiates the formation of biofilms and offers myriad advantages to bacteria. Burgeoning antibiotic resistance in biofilm-producing bacteria has motivated efforts toward finding new alternatives to these traditional antimicrobials. In the present study, we report the increased solubility and additional quorum quenching as well as biofilm disruption activity of glyco-derivatives of monoterpenes (citral and citronellal). Glycomonoterpenes of citral and citronellal were synthesized via conjugation of the monoterpenes with glucose by the non-pathogenic yeast Candida bombicola (ATCC 22214). Structural elucidation of newly synthesized glycomonoterpenes showed that one synthesized using citronellal contains three major lactonic forms with molecular weight 492.43, 473.47, and 330.39 Da whereas the one produced using citral has an acidic form with molecular weight 389.33 and 346.23 Da. The glycomonoterpenes were able to individually inhibit QS, mediated through various medium-chain and long-chain N-acyl homoserine lactones (AHLs). These new compounds are interesting additions to the known range of quorum sensing inhibitors (QSIs) and could be further explored for potential clinical applications.